2018
DOI: 10.1111/jfs.12471
|View full text |Cite
|
Sign up to set email alerts
|

Cetylpyridinium chloride direct spray treatments reduce Salmonella on cantaloupe rough surfaces

Abstract: Cetylpyridinium chloride (CPC) solutions (0, 0.5, or 1.0%) were applied to cantaloupe (“Athena” and “Hale's Best Jumbo” cultivars) rind plugs, either before or after inoculation with a broth culture of Salmonella Michigan (109 CFU/mL) and held at 37°C for 1 or 24 hr. Rind plugs were diluted, shaken, and sonicated, and solutions were enumerated. Texture quality and color were evaluated over 14 days storage at 4°C after 0 and 1% CPC spray applications. A 0.5 or 1.0% (vol/vol) application of CPC after Salmonella … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Additionally, CPC has antibacterial effects on food-borne Salmonella spp. and is used to disinfect various food products including poultry meat [13,23,24]. CPC has the lowest level of risk (level 1) for safety as classified by the United States Food and Drug Administration (FDA) [25], suggesting its high safety.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, CPC has antibacterial effects on food-borne Salmonella spp. and is used to disinfect various food products including poultry meat [13,23,24]. CPC has the lowest level of risk (level 1) for safety as classified by the United States Food and Drug Administration (FDA) [25], suggesting its high safety.…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of QACs in eliminating food pathogens has been extensively studied. It is reported 3–5 log reductions of Salmonella, E. coli, L. monocytogenes, and Yersinia enterocolitica in different MPFV ( Kang et al, 2019 ; Saucedo-Alderete et al, 2018 ; Velázquez et al, 2009 ). For instance, Kang et al (2019) reported 3.33, 3.28, and 4.54 log reductions against E. coli O157:H7, S. enterica serovar Typhimurium, and L. monocytogenes , respectively, on spinach leaves.…”
Section: Conventional Disinfection Methods: Chemical Compoundsmentioning
confidence: 99%
“…For instance, Kang et al (2019) reported 3.33, 3.28, and 4.54 log reductions against E. coli O157:H7, S. enterica serovar Typhimurium, and L. monocytogenes , respectively, on spinach leaves. Regarding the organoleptic properties of MPFV, some studies showed no effect when QACs-based disinfectants were used on spinach leaves and cantaloupe rind plugs ( Kang et al, 2019 ; Saucedo-Alderete et al, 2018 ), but Velázquez et al (2009) reported small spots of yellowish appearance on lettuce leaves and tomatoes.…”
Section: Conventional Disinfection Methods: Chemical Compoundsmentioning
confidence: 99%
“…CPC is an approved poultry washing agent in the US and EU (21 CFR 173.375: FDA 2003) and is marketed as Cecure by safe foods corporation in the US. (13)…”
Section: Properties Of Cpc 31 Antimicrobial Propertymentioning
confidence: 99%